Building theory on monetary retention regimes - Abeysekera, V; Raina, P; Neitzert, T (AUT University, 2009)
The aim of this paper is to explore and recommend a rational basis for setting up a retention regime for a given project. Despite a century of practice, there is no theory to provide guidance yet. Using insights gained from the recently developed theories on monetary retentions, this study argues that retention regimes should be designed to cater for the needs of those who have the power to control. Citing this as an important discovery, the study focuses on public clients and proposes three main objectives to be achieved and a tentative methodology for doing so in the pursuit of knowledge on how to set up a retention regime to cater for a wide variety of needs.
Keywords: Monetary retentions; Retentions; Retainage; Theory